2018 IEEE-RAS 18th International Conference on Humanoid Robots (Humanoids) 2018
DOI: 10.1109/humanoids.2018.8624985
|View full text |Cite
|
Sign up to set email alerts
|

Position and Attitude Control of an Underactuated Flying Humanoid Robot

Abstract: Failure detection and fault tolerant control are fundamental safety features of any aerial vehicle. With the emergence of complex, multi-body flying systems such as jetpowered humanoid robots, it becomes of crucial importance to design fault detection and control strategies for these systems, too. In this paper we propose a fault detection and control framework for the flying humanoid robot iRonCub in case of loss of one turbine. The framework is composed of a failure detector based on turbines rotational spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In the second case, snake aerial manipulators can be seen as discrete systems powered by the action of propellers and thus, they lay the preliminary notions for the study of continuous systems driven through valves and pneumatic or hydraulic fluids, leaving in this case the open problem on the efficiency between using actuators based on the motor-propeller interaction or those based on valves and flows. Concerning to flying humanoids, snake aerial manipulators can be seen as the subsystems or limbs of this kind of robots [45]- [47]. Finally, with respect to non-flying vehicles it must be indicated that extrapolations of the topics described in this text to vehicles different from aircraft can be found at [48]- [52].…”
Section: Applications and Drawbacksmentioning
confidence: 99%
“…In the second case, snake aerial manipulators can be seen as discrete systems powered by the action of propellers and thus, they lay the preliminary notions for the study of continuous systems driven through valves and pneumatic or hydraulic fluids, leaving in this case the open problem on the efficiency between using actuators based on the motor-propeller interaction or those based on valves and flows. Concerning to flying humanoids, snake aerial manipulators can be seen as the subsystems or limbs of this kind of robots [45]- [47]. Finally, with respect to non-flying vehicles it must be indicated that extrapolations of the topics described in this text to vehicles different from aircraft can be found at [48]- [52].…”
Section: Applications and Drawbacksmentioning
confidence: 99%
“…Extensions of this work concern the analysis of the trim condition for specific classes of vehicles. Another future direction is clearly the extension to the three-dimensional case, and eventually to flying multi-body robots [20], [21] that would involve more complex aerodynamics effects.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…It follows from (21) that at any time t there exists an orientation θ 0 (t) such that θ = θ 0 (t) yields α r (t) = 0, i.e. θ = θ 0 (t) = γ r (t) − π ⇒ α r (t) = 0.…”
Section: Proof Of Theorem 1 Proof Of the Item I)mentioning
confidence: 99%
“…Hexapod-quadrotors, insect biobots, and humanoid robots with thrusters are examples of platforms that combine different degrees of locomotion, thus requiring advanced control and modeling methods [7], [8], [10]- [12]. In this category of platforms there is iRonCub, a prototype of flying humanoid robot currently developed at the Italian Institute of Technology [9], [14], [15], [17]. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%